zadanie 71 strona 253 podręcznik przykłady od przykładu e do przykładu h

Odpowiedź:
Szczegółowe wyjaśnienie:
[tex]e) 1\frac{4}{5} - \frac{2}{5} : \frac{5}{4} = 1\frac{4}{5} - \frac{2}{5} * \frac{4}{5} = 1\frac{4}{5} - \frac{8}{25} = \frac{81}{25} - \frac{8}{25} = \frac{73}{25} = 2\frac{23}{25}\\\\\\f) 3\frac{3}{4} : \frac{2}{3} : 8 + \frac{1}{8} * \frac{16}{5} = \frac{15}{4} * \frac{3}{2} * \frac{1}{8} + \frac{2}{5} = \frac{45}{64} + \frac{2}{5} = \frac{45*5}{64*5} + \frac{2* 64}{5*64} = \frac{353}{320} = 1\frac{33}{320}\\[/tex]
[tex]g)(1\frac{1}{2} )^{2} - (\frac{2}{3})^2 : 2 = \frac{9}{4} - \frac{4}{9} * \frac{1}{2} =\frac{9}{4} - \frac{2}{9} = \frac{81}{36} - \frac{8}{36} = \frac{73}{36} = 2\frac{1}{36}\\\\\\h) (1\frac{2}{3})^2 + \frac{5}{18} : \frac{1}{2} = \frac{25}{9} + \frac{5}{18} * 2 = \frac{25}{9} + \frac{5}{9} = \frac{30}{9} = \frac{10}{3} = 3\frac{1}{3}[/tex]